Widget based automated rigging of bipedal character with custom manipulators - Shah, Asadullah; Zeeshan Ahmed, Bhatti (2012)

(untitled)
In this research paper we present an automated rigging system for a humanoid (biped) character with complete customization and control options according to the need of the character rigger and the animator. The rigging requirements check list has been proposed for each body part by analyzing various live natural human motions and then summarizing them. The system initially provides widgets that represent human skeletal joints, which can be easily manipulated and modified according to the character type and body height. The system takes the widgets positions from the 3D space and creates the joint based skeletal structure automatically using procedural programming and then followed by creating a complete bipedal rig with custom manipulators to satisfy the animators need in a production environment.